Logic Model-Based Evaluation of Desa Migran Produktif Empowerment Program in Pati Regency - Azzahra, Ni Made Ray Rika; Nurwati, Nunung; Apsari, Nurliana Cipta (GoAcademica Research & Publishing, 2025)
Desa Migran Produktif (Desmigratif) program aims to empower Indonesian Migrant Workers (IMW) and their families in managing remittances productively to improve welfare and reduce circular migration. However, the implementation in Pati Regency still faces various obstacles. This study evaluates the effectiveness of the Desmigratif Program using a Logic Model approach that includes inputs, activities, outputs, outcomes, and impacts, and analyzes empowerment using Perkins' theory. The method used is qualitative with an evaluative approach through interviews, observations, and documentation studies. The results show that the program has provided assistants, migration services, and productive business training, but is still constrained by limited resources and funding. Migration services and training have been running, but the application of business skills is still limited. Awareness of safe migration has increased, but utilization of remittances for productive businesses is still low. The long-term impact of reducing circular migration has not been significant. Supporting factors include government support and community participation, while the main constraints are the lack of local regulations, limited capital, and suboptimal coordination. Recommendations include strengthening the capacity of officers, mentoring PMI, optimizing program implementation, and improving regulations and funding support for program sustainability.